FAKTOR - FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS TELUK TIRAM KOTA BANJARMASIN TAHUN 2024 - Sari, Elli Novita; Zakiah, Zakiah; Megawati , Megawati; Dewi , Vonny Khresna (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: Anemia is a body condition which is characterized by a blood test results that show the hemoglobin (Hb) level is lower than normal, which is can be caused by an insufficient number of red blood cells, or the number of red blood cells is sufficient but the Hb content in the red blood cells is insufficient (Ministry of Health, 2023). Objective: knowing the factors that influence the incidence of anemia in pregnant women in the working area of Teluk Tiram Community Health Center, Banjarmasin City in 2024. Method: This research uses quantitative methods with an analytical, cross- sectional research design. This research sample was taken using technical methods Probability Sampling, Simple Random Sampling, determining the sample size using the Krejcie and Morgan table, which is 181. Secondary data from registers and e-Cohort. The data were analyzed using the chi-square test with a significance p value = 0.05. Results: there is a significant influence between KEK and the incidence of anemia in pregnant women (p value = 0,009, Odds Ratio Estimate = 6,016). And there is no significant influence between age (p value = 0.716), parity (p value = 0.851), pregnancy spacing (p value = 0.383), and education (p value = 0,068). Conclusion: There was a significant influence between CED and the incidence of anemia with an odds ratio of 6.016 times in pregnant women. The community health centers can further socialize about the importance of health checks at least 6 months before marriage, and hold health education programs about ”ISI PIRINGKU”.